Efficacy of self-assembling peptide in mitigating delayed bleeding after advanced endoscopic resection of gastrointestinal lesions: A meta-analysis - Gopakumar, Harishankar; Vohra, Ishaan; Sharma, Neil R.; Puli, Srinivas R. (Endoscopy International Open, 2023)
Background and study aims Advanced endoscopic resection techniques carry a risk of delayed bleeding (DB). A novel fully synthetic self-assembling peptide (SAP) has shown promising results in mitigating this risk. In this meta-analysis, we evaluated all available data and analyzed the effectiveness of SAP in reducing DB after advanced endoscopic resection of gastrointestinal luminal lesions.Patients and methods Electronic databases (PubMed, Embase, and Cochrane Library) from January 2010 through October 2022 were searched for publications addressing the use of SAP solution in patients undergoing advanced endoscopic resection of gastrointestinal lesions. Pooled proportions were calculated using fixed (inverse variance) and random-effects (DerSimonian-Laird) models.Results The initial search identified 277 studies, of which 63 relevant articles were reviewed. The final analysis included data from six studies comprising 307 patients that met inclusion criteria. The pooled rate of DB was 5.73 % (95 % confidence interval [CI] = 3.42–8.59). Mean patient age was 69.40 years ± 1.82. The weighted mean size of resected lesions was 36.20 mm (95 % CI = 33.37–39.02). Endoscopic submucosal dissection was used in 72.69 % (95 % CI = 67.62–77.48), while endoscopic mucosal resection was used in 26.42 % (95 % CI = 21.69–31.44) of the procedures. Among the 307 patients, 36 % were on antithrombotic medications. No adverse events (AEs) were attributable to using SAP, with a pooled rate of 0.00 % (95 % CI = 0.00–1.49).Conclusions SAP solution appears promising in reducing post-procedural DB after advanced endoscopic resection of high-risk gastrointestinal lesions with no reported AEs.